Microwave diagnostic system of the Uragan-2М torsatron - Sitnikov, D.A.; Berezhnyj, V.L.; Larin, Y.V.; Maznichenko, S.M.; Ocheretenko, V.L.; Pinos, I.B.; Prokopenko, A.V.; Skibenko, A.I.; Tarasov, M.I. (Вопросы атомной науки и техники, 2008)
The construction of microwave sections together with results of loss calculation in the microwave lines for different frequencies are presented. The construction of microwave lead-ins is also described. The whole system has been well-tested on the Uragan-2M torsatron in conditions of SHF and RF cleaning at a low magnetic field, and of pulse regime with a higher magnetic field up to 6 kOe. The results of testing are illustrated by temporal evolutions of plasma density and by digitalized signals from the detector. Представлено конструкції НВЧ-трактів з розрахунком втрат в лініях на різних частотах і конструкції НВЧ- введень. НВЧ-комплекс, що описано, був випробуваний на торсатроні Ураган-2М в режимах НВЧ- і ВЧ- чищення при низькій напруженості магнітного поля, а також в імпульсному режимі з магнітним полем до 6 кЕ. Результати вимірювань ілюструються часовими залежностями густини і цифровими сигналами, отриманими з детектора. Представлены конструкции СВЧ-трактов с расчетом потерь в линиях на различных частотах и конструкции СВЧ-вводов. Описанный СВЧ-комплекс испытан на торсатроне Ураган-2М в режимах СВЧ- и ВЧ- чистки при низкой напряженности магнитного поля, а также в импульсном режиме с магнитным полем до 6 кЭ. Результаты измерений иллюстрируются временными зависимостями плотности и цифровыми сигналами, полученными с детектора.